Analizando los incentivos y beneficios Tributarios en el Ecuador: el sector Floricultor exportador habitual y su incidencia en la recaudación fiscal período 2014-2018. - Salgado Flores, Jhanina Lilibeth (2021)
The Tax Administration, through current regulations, granted taxpayers benefits and tax incentives that are in line with economic activity, in order to boost employment, refute evasion and make the tax progressive; the export floriculture sector sought to enhance its products and strengthen global competitiveness by reducing the tax burden. In this research, the incidence of tax collection was analyzed against the tax incentives and benefits applied by the usual export floriculture sector during 2014-2018; and in this way establish if the tax policy was adequate and equitable for this sector. The applied methodology was descriptive statistics, a quantitative approach was used with the data provided by the Tax Administration through the Center for Fiscal Studies (CEF), to obtain the results of tax incentives and benefits. As a result of the investigation, it was identified that the export floriculture sector is the one who obtains the greatest benefit by becoming a creditor of these tax shields that allow them to reduce the tax burden. When evaluating the fiscal quantifications, it was determined that the State generates a higher tax expense in the Refund of VAT to habitual exporters, by offsetting these items in credit notes or through bank accreditation.